An Eastern Hepatobiliary Surgery Hospital/Portal Vein Tumor Thrombus Scoring System as an Aid to Decision Making on Hepatectomy for Hepatocellular Carcinoma Patients With Portal Vein Tumor Thrombus: A Multicenter Study. Issue 5 (12th March 2019) - Zhang, Xiu‐Ping; Gao, Yu‐Zhen; Chen, Zhen‐Hua; Chen, Min‐Shan; Li, Le‐Qun; Wen, Tian‐Fu; Xu, Li; Wang, Kang; Chai, Zong‐Tao; Guo, Wei‐Xing; Shi, Jie; Xie, Dong; et al.
Abstract : Portal vein tumor thrombus (PVTT) is a significant poor prognostic factor for hepatocellular carcinoma (HCC). Patients with PVTT limited to a first‐order branch of the main portal vein (MPV) or above could benefit from negative margin (R0) liver resection (LR). An Eastern Hepatobiliary Surgery Hospital (EHBH)/PVTT scoring system was established to predict the prognosis of HCC patients with PVTT after R0 LR and guide selection of subgroups of patients that could benefit from LR. HCC patients with PVTT limited to a first‐order branch of the MPV or above who underwent R0 LR as an initial therapy were included. The EHBH‐PVTT score was developed from a retrospective cohort in the training cohort using a Cox regression model and validated in a prospective internal validation cohort and three external validation cohorts. There were 432 patients in the training cohort, 285 in the prospective internal validation cohort, and 286, 189, and 135 in three external validation cohorts, respectively. The score was calculated using total bilirubin, α‐fetoprotein (AFP), tumor diameter, and satellite lesions. The EHBH‐PVTT score differentiated two groups of patients (≤/>3 points) with distinct long‐term prognoses (median overall survival [OS], 17.0 vs. 7.9 months; P < 0.001). Predictive accuracy, as determined by the area under the time‐dependent receiver operating characteristic curves (AUCs; 0.680‐0.721), was greater than that of the other commonly used staging systems for HCC and PVTT. Conclusion: The EHBH‐PVTT scoring system was more accurate in predicting the prognosis of HCC patients with PVTT than other staging systems after LR. It selected appropriate HCC patients with PVTT limited to a first‐order branch of the MPV or above for LR. It can be used to supplement the other HCC staging systems.